2009
DOI: 10.4085/1062-6050-44.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Head Impacts During High School Football: A Biomechanical Assessment

Abstract: Main Outcome Measure(s): Biomechanical variables (linear acceleration, rotational acceleration, jerk, force, impulse, and impact duration) related to head impacts were categorized by session type, player position, and helmet impact location.Results: Differences in grouping variables were found for each impact descriptor. Impacts occurred more frequently and with greater intensity during games. Linear acceleration was greatest in defensive linemen and offensive skill players and when the impact occurred at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
260
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(297 citation statements)
references
References 24 publications
30
260
5
2
Order By: Relevance
“…For the peak LA frequency distribution, both during the games and practice sessions, the range of 10 g ≤ X < 15 g was the most frequent, and the distributions were largely skewed towards low values, supporting previous reports [11][12][13][19][20][21][22][23][24][25] . However, the played over four 15-min quarters in the USA, it is played over four 12-min quarters in Japan, a shorter time period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For the peak LA frequency distribution, both during the games and practice sessions, the range of 10 g ≤ X < 15 g was the most frequent, and the distributions were largely skewed towards low values, supporting previous reports [11][12][13][19][20][21][22][23][24][25] . However, the played over four 15-min quarters in the USA, it is played over four 12-min quarters in Japan, a shorter time period.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, the development of HITS, which collects impact information from the acceleration sensor attached inside the helmet and the sideline response system, which transmits the data, has made it possible to collect collision data from players on actual fields [9][10][11][12][13][19][20][21][22][23][24][25][26][27][28] . However, HITS only measures LA, and RA had to be estimated 28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly three-quarters (74%) of the studies 6-9, 12-16, 20 15 ) and 36ms (HIC 36 ). 8,90 No study reviewed reported the Generalised Acceleration Model for Brain Injury Threshold (GAMBIT) 77,78 or the Head Impact Power (HIP) 79 in their assessment of head impact biomechanics.…”
Section: Head Impact Resultsmentioning
confidence: 99%
“…Based on the differences observed in this study, at the 14.4g threshold there could have been as many as 42% of the impacts recorded not being reported. As a result, studies 7,8,[12][13][14][15]20, 27, 33, 94, 107, 115, 119 using impact thresholds above 10g may have removed 2,100 to 206,573 impacts (see Table 2). At the 30g impact threshold it can be estimated that 80 to 85% of impacts were not reported.…”
Section: Impact Thresholdmentioning
confidence: 99%